Draft Genome Sequences of 3 Strains of Apilactobacillus kunkeei Isolated from the Bee Gut Microbial Community - Crovadore, Julien (Microbiol Resour Announc, 2021)
Apilactobacillus kunkeei is a fructophilic lactic acid bacterium found in fructose-rich environments such as flowers, fruits, fermented food, honey, and honeydew, as well as in the guts of fructose-feeding insects. We report here the draft genome sequences of three Apilactobacillus kunkeei strains isolated from the gut microbial community of three honeybees.